Optimal rolling manoeuvres with very flexible wings - Maraniello,S; Palacios,R (AIAA Journal, 2017)
The single-shooting method is used to identify optimal manoeuvres in the lateral dyna-mics of partially-supported flexible wings. Efficient actuation strategies are sought whenlarge wing deflections substantially modify the geometry of the vehicle during the man-oeuvre. For that purpose, geometrical nonlinear models are first built using compositebeams and an unsteady vortex lattice, and the optimal control problem is then solved via agradient-based algorithm. A flight-dynamics model based on elastified stability derivativesis shown to capture the relevant dynamics either under slow actuation or for stiff wings andit is used as a reference. Embedding the full aeroelastic description into the optimisationframework expands the space of achievable manoeuvres, such as quick wing response withlow structural vibrations or large lateral forces with minimal lift losses.